ANALISIS PENGENDALIAN PROSES PRODUKSI UNTUK MENINGKATKAN KUALITAS PRODUK PADA PERUSAHAAN ELEKTRONIK DI BATAM - Ratna Sari,; Putu Rani Susanthi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to analyze the control of the production process of electronic components, determine the level of product damage, the type of product damage, and the factors that affect the control of production quality at the Electronics Company in Batam. The results of the analysis show that the level of damage to the production of Electronic Companies during the month of Oct-Dec 2019 that occurred in production was 1831 pcs. The average damage in each production is 0.05%. Compared with the company's target of damage, every time the production activity is 1%, it has met the target of the amount of production. The types of damage that often occur in production are dirty pins with a total of 1226 pcs damage, 267 pcs insufficient solder, over soldering, drop part, excess flux which are 187, 148 and 3 pcs respectively. Based on the results of the causal diagram analysis, it can be seen that the factors causing damage in production are derived from human factors/workers, production machines, work methods, materials/raw materials and work environment.